A Pilot Study of an Endoluminal-Suturing Device as a Treatment Strategy for Patients With Obesity and Obstructive Sleep Apnea - Olivier Taton; Michael Fernandez Y. Viesca; Hassane Njimi; Pauline Van Ouytsel; Matthieu Hein; Vincent Huberty (Sleep Medicine Research, 2024)
Background and Objective Obstructive sleep apnea (OSA) is a multifactorial disease, and obesity is the most prevalent risk factor for OSA. Endoscopic sleeve gastroplasty (ESG) is a minimally-invasive procedure used for treating obesity. This prospective study tested the potential benefit of weight loss via an ESG device, endomina®, for reduction of apnea-hypopnea index (AHI) in patients with class I obesity and severe OSA. Methods Ten patients with BMI values of 28 to 34.9 kg/m2 and severe OSA underwent ESG and lifestyle management for 6 months. Patients underwent polysomnography before and 6 months after the endoscopic procedure. The primary endpoint was the percentage of AHI reduction six months after the endoscopic procedure. Secondary endpoints were the proportion of patients with AHI reductions of 50% six months after ESG, improvements in respiratory parameters and sleepiness, effectiveness on weight loss, and correlations with decreased AHI. Results Patients experienced 54% (±11%) reductions in AHI. Seven patients had an AHI reduction of ≥50%, and five had an AHI of <15 events/h. Total body weight loss (TBWL) and excess weight loss (EWL) were 10.1% (±3.4%) and 45.4% (±14.0%), respectively, and there was no correlation between AHI and TBWL/EWL. There was an overall improvement in respiratory sleep parameters after ESG, except for snoring, and a reduction in daytime sleepiness. Conclusions These results suggest that using an ESG device, endomina®, with lifestyle modification for promoting weight loss in class I obese patients with severe OSA is a promising treatment strategy for reducing OSA and improving respiratory parameters and daytime sleepiness.